Implementasi Inquiry Based Learning Berbantuan Pop-Up pada Pembelajaran IPAS - Kholifah, Siti; Mubaidilla, Irfa'i Alfian (Borobudur Educational Review, 2026)
This study aims to examine the effect of the Inquiry Based Learning model assisted by Pop-Up Book media on students’ learning motivation and cognitive ability in science and social learning at the elementary level. The study used a quantitative approach with a one group pretest-posttest design involving 20 third-grade students. Data were collected through tests and questionnaires, then analyzed using statistical techniques including normality test, homogeneity test, and paired sample t-test with SPSS 24. The results showed a significant improvement in both learning motivation and cognitive ability after the implementation of the learning model. Statistical analysis indicated that the significance value was less than 0.05, confirming a meaningful difference between pretest and posttest scores. The findings suggest that active learning through inquiry processes combined with interactive visual media can enhance student engagement and understanding. In conclusion, the Inquiry Based Learning model supported by Pop-Up Book media is effective in improving learning motivation and cognitive outcomes in elementary education.